Peculiarities of hardware implementation of generalized cellular tetra automaton - Аноприенко, Александр Яковлевич; Федоров, Евгений Евгениевич; Иваница, Сергей Васильевич; Альрабаба, Хамза (Technology audit and production reserves, 2015)
Cellular automata are widely used in many fields of knowledge for the study of variety of complex real processes: computer engineering and computer science, cryptography, mathematics, physics, chemistry, ecology, biology, medicine, epidemiology, geology, architecture, sociology, theory of neural networks. Thus, cellular automata (CA) and tetra automata are gaining relevance taking into account the hardware and software solutions. Also it is marked a trend towards an increase in the number of possible states of CA that led to the emergence of new types of CA, which are united in this paper under a common name – postbinary cellular automata. This article proposes a variant of generalized structure of CA cell using asynchronous data storage device, software configurable via the user interface. Several ways of hardware implementation of initial values record in register of the cell status and read the results from the current layer of states in the register of reading the results: serial, block, using a layer of initial states through direct serial or block addressing, or cascade addressing on the basis of tetracodes. It is considered the CTA structure when used as a coprocessor in the local computers. At the same time the detailed descriptions are given, problems are identified, corresponding schematic structure are given. It is considered in detail the generalized block diagram of a multi-layer cellular automaton and it is proposed a generalized block diagram of a multi-layer CA cell that improves performance and extended functionality compared with the known CA. The main advantage of the proposed implementation of cellular automata is functional diversity of elements and flexibility, the ability to change the laws of transitions immediately in all cells (matrix elements). Therefore, CA mass production (as well as CTA) on this technology can get a testing ground for numerous experiments in various fields of science.